2018
DOI: 10.1063/1.5019784
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity, surface tension, density and contact angle of selected PbI2, PbCl2 and methylammonium lead halide perovskite solutions used in perovskite solar cells

Abstract: Perovskite solar cells (PSCs) are currently under vigorous research and development, owing to their compelling power conversion efficiencies. PSCs are solution-processed and, therefore, are fabricated using casting and printing methods, such as spin, spray and blade coating. The coating characteristics significantly depend on the physical and rheological properties of the solutions. Thus, due to the scarcity of such properties, in this work, we report the surface tension, viscosity, density, and contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…The slight recovery of hydrophobicity with longer UVO exposure time is probably attributed to loss of low molecular weight organic material that has been created on the surface during UVO treatment and reorientation of side groups on the molecules due to the burying of newly formed polar groups in the exposure region . The smallest contact angle 24.2° is obtained by exposure under UVO for 5 min, which facilitates the formation of a more uniform perovskite layer . The current–voltage ( I–V ) characteristics have been measured under dark condition to determine the effect of UVO treatment on the electrical conductivity of the NiO x film (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The slight recovery of hydrophobicity with longer UVO exposure time is probably attributed to loss of low molecular weight organic material that has been created on the surface during UVO treatment and reorientation of side groups on the molecules due to the burying of newly formed polar groups in the exposure region . The smallest contact angle 24.2° is obtained by exposure under UVO for 5 min, which facilitates the formation of a more uniform perovskite layer . The current–voltage ( I–V ) characteristics have been measured under dark condition to determine the effect of UVO treatment on the electrical conductivity of the NiO x film (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Modifications of the CA by less than 5° were shown to directly result in higher conductive conjugated polymer‐based contacts in organic solar cells 64. For perovskite solar cells, it was reported that small variations in CA yield to macroscopic differences in film formation which directly affects the efficiency 65. Menzies and Jones correlated slight changes in CAs to immediate changes in cell–cell interactions in tissue engineering 21…”
Section: Resultsmentioning
confidence: 99%
“…However, in the latter process, the synthesis is difficult to control as the perovskite grows extremely fast in the solution. Therefore, dipping times are usually less than 1 min . Actually, perovskite thin films, prepared on a flat substrate by the spin‐coating technique, suffer from pinholes and the reduced surface coverage, which may affect photovoltaic cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, perovskite thin films, prepared on a flat substrate by the spin‐coating technique, suffer from pinholes and the reduced surface coverage, which may affect photovoltaic cell performance. Since these methods are liquid‐based methods, the liquid properties such as viscosity, surface tension, and density of the solution affect seriously the resulting films' properties, especially the growth mechanism and film morphology . Beside this, in spin coating, the radial force due to spinning velocity controls the liquid dynamics and film thinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation